Monte Carlo-based analysis of the photon beam fluence with air gap thickness between Linac head exit window and patient’s skin in radiotherapy treatments - Mohamed Bencheikh; Abdelmajid Maghnouj; Jaouad Tajmouati (Ядерна фізика та енергетика)
Linear accelerators (Linac) are used in radiation therapy treatment and its technology improvement ensures high dosimetry quality that should be conserved for high radiotherapy efficiency. However, does the air gap between the exit window of Linac head and patient’s skin alters the physical properties of the photon beam? The objective of this study is to assess the physical properties changes of photon beam fluence according to air gap thickness under the Linac head. The air gap under the Linac head is the last material in the photon beam path; it induces alterations in the beam quality before reaching the patient’s skin. The Varian Clinac 2100 head and the air gap up to the phantom surface are modelled using Monte Carlo BEAMnrc code; the nominal beam energy is 6 MV. The BEAMDP code is used to extract the photon fluence. The photon beam fluence is affected by the air gap under Linac head and decreases by six times due to the photon beam attenuation with air gap thickness; in addition to increasing of beam contamination by scattered photons and electrons. Thus, the air gap induces the beam quality deterioration which is evaluated in terms of photon fluence with air gap thickness. To remove the particles contaminations and conserve integrally the photon beam quality, the number of the photon interactions with air atoms should be as low as possible under Linac head up to patient’s skin and ensure a higher quality of the radiotherapy treatment of deep tumour.